Livelihood of Nepali Migrant Workers - Shahi, Hari Bhakta; Neupane, Ujwol (Innovative Research Journal, 2026)
People migrate for the quality of life. Lively hood mainly depend on income , social status, quality education and health. It is found that there is significant growth of labor migration to japan, Korea and European countries . Economic improvement directly boost housing, health, education and minimizing poverty of MWs . Thus FE is the powerful economic force that reshape household assets, social structure and individual capabilities, directly impacting local livelihood and broader socio economic landscape. Majority of youth choose Gulf and Malaysia for FE, After 2022 the trend has shifted towards the Europe, South Korea and japan .male MWs is higher than the female MWs. According to DoFE 2024; Labor approval was issued largely to the skilled MWs (72.9% male, 62.7% female) which is good for Nation. Death of Nepali young MWs is serious matter in FC; every day 2 to 4 death body is reaching in Nepali’s airport. Returnee MWs had Mainly choose agriculture sector (21.5% male and 33.5% female) followed by self-employment (27% male and 17% female). Un-appropriate job placement, excessive service fee, difficulties in workplace caused by language barriers, increasing number of injury and death of MWs, divorcee, family detachment and family conflicts are visible challenge of Nepali MWs. Despite of challenge; foreign employment remains maim alternative due to job creation, poverty reduction , skill transfer, quality education, vocational training, business investment, experience share and ICT. Thus lively hood of Nepali MWs is increased with certain challenge.